2017
DOI: 10.1186/s12872-017-0610-6
|View full text |Cite
|
Sign up to set email alerts
|

The unique value of cardiovascular magnetic resonance in patients with suspected acute coronary syndrome and culprit-free coronary angiograms

Abstract: BackgroundPatients with chest pain, elevated troponin, and unobstructed coronary disease present a clinical dilemma. The purpose of this study was to investigate the incremental diagnostic value of cardiovascular magnetic resonance (CMR) in a cohort of patients with suspected acute coronary syndrome (ACS) and unobstructed coronary arteries.ResultsData files of patients meeting the inclusion criteria in two cardiology centres were searched and analysed. The inclusion criteria included: 1) thoracic pain suspecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Based on these findings, a novel diagnostic algorithm proposed by Patriki et al led to an average 4.9fold increase in the rate of myocarditis detection over two subsequent years. 67,[124][125][126][127][128][129][130][131]…”
Section: Cmr Imagingmentioning
confidence: 99%
“…Based on these findings, a novel diagnostic algorithm proposed by Patriki et al led to an average 4.9fold increase in the rate of myocarditis detection over two subsequent years. 67,[124][125][126][127][128][129][130][131]…”
Section: Cmr Imagingmentioning
confidence: 99%
“…The results showed subendocardial infarction in 24% , myocarditis in 38%, TS in 16% and 21% patients with normal CMR 4 . There are several studies, mostly retrospective, that used CMR in MINOCA with similar results regarding myocardial infarction (16-26%) but great variation regarding myocarditis (27-54%) and normal cardiac MRI (0-30%) [74][75][76][77][78][79][80][81][82] . The time from coronary angiography to CMR is probably of importance and varied between 3-10 days in these studies ( Table 2).…”
Section: Minoca and Cmr Imagingmentioning
confidence: 99%
“…18 Once this shows no epicardial coronary disease characterization and help differentiate it from myocarditis. 19 Usually, it is only in retrospect that the diagnosis can be made with certainty, once the wall-motion abnormalities fully resolve after a few days or weeks and the typical clinical picture becomes more evident. Studies have reported an incidence of TC of 1%-2% among patients presenting with a clinical syndrome of ACS.…”
Section: Introductionmentioning
confidence: 99%
“…Often, invasive coronary angiography is the first diagnostic test in a patient with acute chest pain and elevated cardiac biomarkers, especially if there is ST elevation or ongoing chest pain 18. LA = left atrium; LV = left ventricle; RV = right ventricle characterization and help differentiate it from myocarditis 19. Other imaging modalities such as echocardiography and CMR can be very useful in this regard because they show the typical nature of wall-motion abnormalities, and CMR can also provide tissue F I G U R E 1 Initial echo (apical 4-chamber view) with LVEF 35%, hypokinesis of mid-and apical LV, preserved basal contractility and a large, mobile apical LV clot (arrow).…”
mentioning
confidence: 99%